SAT0100 Increased Vascular Wall Inflammation in Patients with Early Rheumatoid Arthritis as Measured by 18F-FDG-PET/CT. (9th June 2015) - Agca, R.; van Sijl, A.M.; Smulders, Y.M.; Voskuyl, A.E.; van der Laken, C.J.; Boellaard, R.; Lensen, K.-J.D.; Nurmohamed, M.T.
Abstract : Background: Patients with rheumatoid arthritis (RA) have an elevated risk of developing cardiovascular disease (CVD). Like RA, atherosclerosis is a chronic inflammatory process. There are indications that aortic inflammation in atherosclerosis can be detected by 18 F-Fluorodeoxyglucose-positron emission tomography/computed tomography ( 18 F-FDG-PET/CT). Objectives: To quantify 18 F-FDG uptake in large arteries of RA patients as compared to controls using PET/CT as a potential marker of vascular wall inflammation in areas of atherosclerosis, and its association with disease activity in patients with RA. Methods: 18 F-FDG-PET/CT studies were performed in patients with active early RA (DAS28 >4.0; median disease duration 12 (8 – 21) days; n=20), active established RA (DAS28 >4.0; median disease duration 8 (3 – 14) years; n=23) and in controls with osteoarthritis (OA; n=15). Semi-quantitative FDG-uptake in the arterial walls was determined by standardized uptake values (SUV) and tissue-to-background ratios (TBR) using 18 F-FDG activity in the vena cava as background. Volumes of interest (VOI) covering an arterial segment were defined to derive the maximum SUV (SUVmax, regional arterial uptake). Global arterial uptake was estimated by using the mean of all regional arterial uptakes in all arteries. Results: Regional as well as global arterial uptake of 18 F-FDG was the highest in patients with early RA as compared to established RA and OA, with significantly higher SUV in the thoracic aortic tract (respectively p=0.009 and p=0.005), the abdominal aorta (respectively p=0.031 and p=0.005) and the femoral arteries (respectively p=0.136 and p=0.016). SUV didn't differ significantly between established RA an OA controls (data not shown). C-reactive protein (CRP) levels were associated with increased global arterial SUV (β=1.15, 95% CI 1.07 – 1.24; P=0.003) as well as increased regional arterial SUV in the thoracic aortic tract (β=1.18, 95% CI 1.06 – 1.30; P=0.006), the iliac arteries (β=1.11, 95% CI 1.03 – 1.19; P=0.016) and the femoral arteries (β=1.18, 95% CI 1.07 – 1.30; P=0.006) in early RA patients and not in established RA (data not shown). DAS28 levels were only associated with SUV levels in early RA (global arterial uptake β=0.162, 95% CI 0.032 – 0.292; P=0.018, thoracic aortic tract β=0.189, 95% CI 0.042 – 0.335; P=0.015, iliac arteries β=0.134, 95% CI 0.012 – 0.257; P=0.034, femoral arteries β=0.164, 95% CI 0.007 – 0.321; P=0.041). There were no significant differences in TBR between both RA groups and OA (data not shown). Conclusions: Increased and predominantly regional vascular wall uptake of 18 F-FDG as sign of vascular inflammation was found in several arterial segments of early RA patients, suggesting atherosclerosis, and was associated with clinical assessments of disease activity. The lack of differences between the established RA and OA controls and the lack of differences in TBR requires further study. Disclosure of Interest: None declared